A System Dynamics of Indonesia Low Carbon Energy Resilience Model - Andi Muhammad Sadli (Mulia Pratama, 2015)
Energy plays an important role shaping civilization as a major input from various sectors of life. For Indonesia, the management and utilization of energy will determine the likely existence as a nation forward in the future. This research used a quantitative methodology which is the chosen method is system dynamic simulation. The system dynamic model is the shape and energy utilization in Indonesia in order to achieve a degree of energy security with complex variables covering economic, social and environmental as well. The model simulation investigates the implications the use of fuel to the economy and how to find a model of low-carbon energy sustainability in the energy mix policy in Indonesia. The model explores the relationship between population, fuel consumption, fuel production, fuel import, and emissions resulting from the use of fuel. This model will be used as the basis for the simulation scenario of Business As Usual (Base case) so that the visible trend of each variable and how interventions should be done. The interventions that are chosen namely structural intervention where included gas and geothermal as the additional energy resources. Then, Hypothesis that would be tested in this research is the reduction of CO2 emission and fossil fuel import as the feedback of energy mix policy. The result shows that mix energy policy is able to reduce the CO2 emission at least 9% in average along the simulation period. In other hand the import of fossil fuel import can be reduced averagely up to 27%. Therefore, the mix energy policy is strongly feasible to be implemented and developed in the future. DOI.10.13140/RG.2.2.29569.35683